Effective adsorption of metronidazole antibiotic from water with a stable Zr(IV)-MOFs: Insights from DFT, kinetics and thermodynamics studies. Issue 1 (February 2020) - Alamgir; Talha, Khalid; Wang, Bin; Liu, Jing-Hao; Ullah, Raza; Feng, Fan; Yu, Jiamei; Chen, Sha; Li, Jian-Rong
Graphical abstract: Abstract: The adsorptive removal of antibiotics, emerging organic pollutants in water is very important but challenging. In this work we report a series of eight water stable metal-organic framework (MOFs), which are methodically screened for the removal of metronidazole (MNZ) from water. It was found that two isostructural Zr(IV)-MOFs (UiO-66 and UiO-66-NH2 ) showed adsorption capacities of around 200.2 mg g −1 and 265.5 mg g −1, respectively, which are higher than the experimental values of reported porous materials used for MNZ removal so far. The MOFs were characterized by Powder X-ray diffraction (PXRD), Fourier transform infrared (FT-IR) spectroscopy, Thermogravimetric analysis (TGA), Scanning electron microscope (SEM), Energy-dispersive X-ray elemental analysis (EDX), BET isotherm, UV–vis (UV–vis) spectrophotometer and NICOMP™ 380 ZLS. The effects of various parameters including time, concentration, temperature and pH were investigated. The adsorption mechanism of UiO-66-NH2 for MNZ has also been explored through computational simulations. The results showed that MNZ molecules are mainly locate at around the -NH2 functional groups in pore surfaces of UiO-66-NH2, with the increase of molecular level of the amino groups, the affinity of the framework to MNZ could be significantly increased. The results demonstrated that highest adsorption uptake by UiO-66-NH2 was attributed to -NH2 functional group including with (hydrogen bonding interactions, electrostatic interaction and larger pHpzc ). The adsorption process of the two MOFs fitted the pseudo-second-order kinetic model and Langmuir isothermal model, whilst the adsorption was endothermic, with the confirmation by thermodynamic studies.